A review on factors to be incorporated in water quality study - Danial Nakhaie Mohd Soukhri,; Siti Multazimah Mohamad Faudzi,; Zuriyati Yusof,; Mohd Fitri Mohd Akhir,; Nurzulaikha Mohd Kamal,; Noor Aida Saad, (Penerbit Universiti Kebangsaan Malaysia, 2022)
Water quality issues had been the main concern in worldwide as water resource keeps being polluted. River acts as the main source of drinking water, habitat for aquatic life, agriculture and industry. Poor in water quality led to the increase n water treatment expenses, water scarcity and affect health. River pollution is caused by industrial discharge, sewage and wastewater, chemical fertilizers and pesticides and mining activities. This paper aims to review and comments on factors to be incorporated in water quality study. Water quality index and pollutants are found to be the critical factors. USA, Canada, Iraq, Thailand, Vietnam and Malaysia used different parameters in calculating WQI. The parameters being considered in the WQI are then classified the river according to their classes and usage. Department of Environment (DOE) Malaysia has highlighted three main pollutants in water quality study which are Biochemical Oxygen Demand (BOD), Ammoniacal Nitrogen (NH3 N) and Suspended Solid (SS) due to their great influence on WQI calculation. However, standard treated water quality in Malaysia is still based on Environmental Quality Act, 1974 which is nearly 50 years ago. Emerging pollutants which are mainly organic compounds present as pharmaceuticals and personal care products are found in water resources nowadays and the treatment should be improvised along time. Some modification of class on usage of water as irrigation should be considered and the relevant of considering two oxygen demands in calculating WQI (BOD and COD).